How Effective Is Correctional Education, and Where Do We Go from Here? The Results of a Comprehensive Evaluation - Lois M. Davis, Jennifer L. Steele, Robert Bozick, Malcolm V. Williams, Susan Turner, Jeremy N. V. Miles, Jessica Sa (RAND Corporation, 2014)
The Second Chance Act of 2007 (Pub. L. 110-199) is a historic piece of legislation designed to improve outcomes for and provide a comprehensive response to the increasing number of individuals who are released from prisons, jails, and juvenile residential facilities and returning to communities upon release. The Second Chance Act’s grant programs are funded and administered by the Office of Justice Programs within the U.S. Department of Justice. In 2010, for the first time, funding was set aside for a comprehensive study of correctional education. The Office of Justice Programs’ Bureau of Justice Assistance awarded the RAND Corporation a cooperative agreement to undertake a comprehensive examination of the current state of correctional education for incarcerated adults and juveniles, where it is headed, which correctional education programs are effective, and how effective programs can be implemented across different settings. Our first report, published in 2013—Evaluating the Effectiveness of Correctional Education: A Meta-Analysis of Programs That Provide Education to Incarcerated Adults—presented a comprehensive review of the scientific literature and a meta-analysis that synthesized the findings from multiple studies on the effectiveness of correctional education programs in helping to reduce recidivism and improve postrelease employment outcomes for incarcerated adults (Davis et al., 2013). This final report to the U.S. Attorney General first presents a summary of the findings from our earlier literature review and meta-analysis on the effectiveness of correctional education programs for incarcerated adults. It also provides three new sections. The first of these is a systematic review of correctional education programs for juveniles. The second is the results of a national survey of state correctional education directors, which provide an up-to-date picture of what the field of correctional education looks like today in the United States and explores the use of computer technology, preparations for the new 2014 GED exam, and the impact of the 2008 recession. We conclude with a set of recommendations, as part of our original charge for this study, on improvements needed to further the field of correctional education. These results will be of interest to federal and state policymakers; administrators of state departments of corrections, public safety, and education; correctional educators and college educators; career technical training providers; and other organizations that provide educational services and training to the currently incarcerated or formerly incarcerated. These results will also be of interest to those in the U.S. Departments of Justice and Education who are committed to ensuring the availability and quality of correctional education programs for incarcerated adults and juvenile